SPESIALISASI MATERI AJAR SEBAGAI UPAYA PENGEMBANGAN PROFESIONALISME GURU - Salirawati, Das (Jurnal Cakrawala Pendidikan, 2010)
Abstract The school-based curriculum gives teachers freedom to design and develop all learning activities for students by themselves, so it is expected that the teachers’ competence can be improved optimally. Besides, teachers’ creativity and innovation can be developed to increase their professionalism. But, the fact shows that the teachers’ responsibility is so heavy that they do not have enough time to develop their professionalism. Almost all SMPs/MTss and SMAs/MAs in Indonesia assign teachers some duties based on classes. One of the ways to improve teachers’ mastery can be done by taking specialization in teaching materials. This method gives some advantages to teachers and students as well. For the teachers, specialization in teaching materials can make them: (1) concentrate on the teaching material development; (2) plan learning strategies effectively; (3) look for references easily and attentively; (4) write summaries and modules; (5) select seminars and workshops to attend; and (6) direct students based on their ability. For the students, specialization in teaching materials can make them: (1) get the unity of concepts from the same teacher; (2) avoid needless character adaptation from different teachers; (3) detect self-ability; (4) look for references easily; and (5) avoid from learning over-lapping concepts. It seems difficult to implement specialization for teaching material, but by having a good intention to increase learning quality in Indonesia, all difficulties and obstacles can be handled. Patience and seriousness are really needed to start a new thing. Whatever the result is, this effort should be made. Keywords : specialization, effort, professionalism, teacher